EFEKTIFITAS DOSIS PUPUK KADANG KAMBING TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KEDELAI ( Glycine max L. Merril ) - Hidayat, Moh Syarif; Samudin, Sakka (AGROTEKBIS : JURNAL ILMU PERTANIAN (e-journal), 2024)
The excessive use of non-organic fertilizers can lead to soil degradation. To address this issue, organic fertilizers, such as goat manure, can be used as an alternative to enhance soil fertility and improve crop production. This study aimed to determine the effective dosage of goat manure fertilizer on the growth and yields of soybean plants (Glycine max L. Merrill). The research was conducted in a screen house at Tadulako University, Palu, from November 2020 to 2021. The study used a Completely Randomized Design (CRD) with one factor: the dosage of goat manure. The treatments included: K0 (no fertilizer added, control), K1 (7 t/ha or 35 g/polybag), K2 (8 t/ha or 40 g/polybag), K3 (9 t/ha or 45 g/polybag), and K4 (10 t/ha or 50 g/polybag). The results of this study are expected to provide insights into optimal goat manure application rates for sustainable soybean cultivation.